Appropriate intensity measures for probabilistic seismic demand estimation of steel diagrid systems. (15th December 2021) - Heshmati, Mahdi; Jahangiri, Vahid
Highlights: Studying about suitable IMs for the steel diagrid systems is not conducted before. Obtaining suitable intensity measures (IMs) is studied considering a set of 38 IMs. Four diagrid structures with 4, 8, 16, and 24 stories are subjected to IDA. Efficiency, practicality, proficiency, sufficiency and scaling robustness are used. It is shown that the suitable IMs for the steel diagrid systems are PGV and PGV/PGA. Abstract: Performance-based earthquake engineering (PBEE) predicts the performance of structures subjected to earthquake ground motions to improve seismic risk mitigation decisions. In PBEE, intensity measures (IMs) are employed as a link between earthquake hazard and seismic response. To the best of the authors' knowledge, investigation of the appropriate IMs for the probabilistic seismic demand evaluation of steel diagrid systems has not been presented in literature so far. In this study, the efficiency, practicality, proficiency, sufficiency, and scaling robustness of 38 candidate IMs for estimating the seismic response of low- to high-rise steel diagrid systems are investigated. Finite-element models of the structures are performed in OpenSees software and subjected to incremental dynamic analysis (IDA) using 22 far-field earthquake records. The whole response of the investigated diagrid systems is captured in terms of maximum inter-story drift ratio (MIDR). The appropriate IMs among the candidate IMs for steel diagrid systems are identified utilizing the concepts of efficiency, practicality, proficiency, sufficiency, and scaling robustness. The regression analysis results showed that peak ground velocity (PGV) and the ratio of PGV to peak ground acceleration (i.e., PGV/PGA) are the most appropriate IMs for seismic response prediction of steel diagrid systems under far-field ground motions. Furthermore, the collapse fragility curves, as well as drift hazard curves, were obtained based on various IMs. It was observed that the proposed IMs reduce the uncertainty in fragility curves. Also, it was concluded that seismic IM has a significant impact on the structural response hazard of steel diagrid systems.